2012
DOI: 10.5301/hip.2012.9042
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Classification of the Neural Anatomy in the Human Hip Joint

Abstract: Hip arthroscopy remains a useful surgical intervention for labral injuries. The literature has predominantly focused on structural and vascular considerations of the hip joint, with few studies examining the neurohistology of the surrounding periarticular tissues. We mapped and identified the periarticular neural anatomy, to identify the presence of sensory nerve fibres and mechanoreceptors within the hip joint. Eight human cadaveric hips were dissected into a total of ten specimens per hip. Histological stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
114
2
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 20 publications
3
114
2
7
Order By: Relevance
“…However, their results are doubtful as mentioned. Our anatomic division is similar with the studies that our findings are in agreement with 2,3 . It was thus reported that anterior labrum contains the highest FNEs and NEOs concentration.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Isupporting
confidence: 83%
See 4 more Smart Citations
“…However, their results are doubtful as mentioned. Our anatomic division is similar with the studies that our findings are in agreement with 2,3 . It was thus reported that anterior labrum contains the highest FNEs and NEOs concentration.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Isupporting
confidence: 83%
“…In our study, FNEs and NEOs were basically detected in ventral (anterior) part of the labrum (zones 1 and 2). This finding is in full agreement with these of two studies 2,3 , in partial agreement with another study 1 , and in full disagreement with the last study 4 Table I. General characteristics of reported studies regarding normal histologic architecture of acetabular labrum.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Isupporting
confidence: 79%
See 3 more Smart Citations